The Secondary School Experience with Chronic Fatigue Syndrome/ Myalgic Encephalomyelitis (CFS/ME): An Interpretative Phenomenological Analysis of the Retrospective Accounts of Young Adults - Davies, Charlotte (2021)
Chronic Fatigue Syndrome/ Myalgic Encephalomyelitis (CFS/ME) is an illness with a range of symptoms, however a core feature is fatigue after physical or mental exertion (NICE, 2007). The illness affects up to 2% of secondary school children (Collard & Murphy, 2019). It is a main cause of prolonged school absence (Crawley et al., 2018), and the impacts raise potential needs across all areas of the SEND Code of Practice (DoH & DfE, 2015). A literature review for the present study found little research had been conducted into the secondary school experiences of children and young people with CFS/ME, as much as the research came from a medical perspective, of which school life was a smaller consideration.